FINANCING STRATEGY TO SUPPORT REQUIRED BUSINESS GROWTH (STUDY CASE: NERTUR) - Fidiantowi, Ridho
NerTur targets an annual revenue of IDR 7.5 billion by 2025. To achieve the target, the required growth rate at 70.17% annually is pretty high. However, the actual growth of the company in 2022 at 81.19% outperforms its sustainable growth rate at 29.28% and it seems achieveable but it requires aggressive expansion across operating systems, inventory, and marketing. Business growth cannot exceed the SGR over an extended period as the growth rate will be held back by the lack of capital and requires financing strategy by considering to changing the capital structure.